Pengaruh Breast Care Terhadap Peningkatan Produksi ASI Pada Ibu Post Partum - ROHANI SIREGAR (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Breast milk is . complete nutrients needed by a baby and also easily digested by a small and sensitive baby's stomach. Breast milk alone is sufficient to meet the nutritional needs of infants from the age of 0-6 months and can be continued until the child is 2 years old. The purpose of this study was to determine the effect of breastcare on increasing milk production in postpartum mothers. The research design is pre-experimental. The design used is the one group pretest posttest design. The data analysis used is the Wilcoxon test. The results showed that there was an effect of breastcare on increasing breast milk production as indicated by a p value of 0.0001 <α 0.05. Suggestions from the study are that postpartum mothers can do breastcare 2 times a day in the morning and evening, because it can help increase milk production and can fulfill the baby's nutrition, so that exclusive breastfeeding is achieved for 6 months without providing additional food in any form except for drugs as indicated. Breastcare education needs to be improved to support the first 1000 days of a child's life